Про деякі методологічні засади вивчення неандертальських поховань - Смирнов, С.В. (Археологія, 1990)
У статті обгрунтовується питання про те, що проблема неандертальських поховань мусить розглядатися як складова частина всього комплексу питань про формування первісного синкретизму на підставі розуміння цілісності антропосоціогенезу. При такому підході неандертальські поховання пов'язуються з генезисом релігії і не можуть оцінюватись як докази вже сформованих релігійних поглядів. Проблема неандертальских погребений — неотъемлемая составная часть более общей проблемы происхождения и ранних форм религии. Неразрывное единство религиозного, этического, эстетического, познавательного и волевого в деятельности первобытного человека диктует необходимость рассмотрения генезиса религии как элемента первобытного синкретизма. Воззрения, будто неандертальские погребения характеризуют уже окончательно сложившуюся религию, противоречат теоретическим исходным принципам решения проблемы генезиса социальности, слабо подтверждаются анализом конкретных данных и фактически упраздняют проблему генезиса религиозных верований. Целостный подход к изучению указанных археологических комплексов с учетом взаимосвязи формирования физических и психических свойств человека, становления индивидуального и общественного (в том числе и религиозного) сознания, языка, труда и порожденных им социальных отношений приводят к выводу о том, что в неандертальских погребениях следует усматривать формирование религиозного культа, следовательно, религиозных верований в целом. A problem on the Neanderthal burial places is an integral part of the more general problem on the origin and early form of the religion. An indissoluble unity of the religious, ethic, aesthetic, cognitive and strong-willed in the activity of a primitive man impels the necessity to consider the genesis of the religion as an element of the primitive syncretism. Views that the Neanderthal burial places characterize the religion formed already once and for all are at variance with theoretical initial principles aimed at solution of a problem of the sociality genesis, are confirmed but slightly by the analyses of particular data and, in fact, abolish a problem of genesis of religious believs. An integral approach to the study of the mentioned archaeological complexes with allowance for the interrelation that exists between formation of physical and psychical properties of man, formation of the individual and social (including the religious) consciousness, language, labour and labour-engendered human relations has promoted a conclusion that origin of the religion and, thus, of religious believs on the whole, roots in the Neanderthal burial places.